THE ROLE OF ISLAMIC LAW IN THE EQUITABLE DIVISION OF JOINT ASSETS POST-DIVORCE WITHIN URBAN SOCIETY: A DESCRIPTIVE STUDY OF ITS APPLICATION IN BANDUNG HIGH RELIGIOUS COURT - Bainon, Masalan; Fautanu, Idzam; Solihin, Dadin; Khosyi’ah, Siah; Hasan Ridwan, Ahmad (AKADEMIKA: Jurnal Pemikiran Islam, 2024)
This research examines the legal certainty of joint property, defined as assets jointly acquired by spouses during marriage, particularly within the context of urban Muslim society. Using a descriptive-analytical method, it explores the relevance of joint property in the lives of married couples and its division post-divorce. The study highlights the legal ambiguities in Indonesia's current framework, particularly in Law No. 1 of 1974 on Marriage and the Compilation of Islamic Law (KHI). These regulations often fail to address modern family dynamics, such as when the wife is the primary breadwinner. This gap has resulted in inconsistent rulings in religious courts, particularly in urban areas where economic roles and gender dynamics are rapidly evolving. Focusing on the Bandung High Religious Court, the research emphasizes the importance of equitable asset division that reflects fairness, justice, and the lived realities of urban Muslim families. Findings suggest that while courts generally provide justice and legal certainty, there is a growing need for updated legal interpretations that accommodate changes in societal roles and expectations.